Kehalalan Vaksin Covid-19 Produksi Sinovac dalam Fatwa MUI dan Implementasi Vaksinasinya Pada Tenaga Kesehatan di Puskesmas Tanjung Morawa, Deli Serdang (Perspektif Qawaidh Fiqhiyyah) - Ibnu Radwan Siddik (Al-Mashlahah: Jurnal Hukum Islam dan Pranata Sosial, 2021)
AbstractThis study aims to find out how the fatwa of the Indonesian Ulama Council (MUI) on the halalness of the covid-19 vaccine produced by Sinovac, the fiqh rules used in the fatwa and the level of accuracy and relevance of the rules used. This study also aims to find out how to implement the use of the covid-19 vaccine produced by Sinovac among health workers of Tanjung Morawa Health Center, Deli Serdang Regency. The research method used is qualitative research using sociological approach and qawaidh al-fiqhiyyah. The results showed that the halal fatwa of covid-19 vaccine produced by Sinovac based on MUI fatwa no. 2 Year 2021 by using three fiqh rules namely al-dhararu yuzal (harm must be eliminated), al-daf'u awla min al-raf'i (preventing more important than eliminating) and yahtamil al-dharar al-khos lidaf'iy al-dhorar al-'am (shouldering / bear certain harms in order to prevent the onset of harm that is evenly distributed). The implementation of this fatwa is strongly felt by health workers in the Tanjung Morawa Health Center, Deli Serdang Regency. The halal covid-19 vaccine produced by Sinovac adds to the readiness of health workers to receive vaccines. Health workers who are Muslims are also aware of the consideration of fiqh rules in the MUI fatwa. side effects of vaccines that have been feared by some people turned out not to be experienced significantly by health workers who have been vaccinated, this adds to the level of accuracy of the fiqh rules used by MUI in consideration of the evidence in its fatwa.